Зубчатые передачи с пластмассовыми колесами: программа автоматизированного проектирования - Старжинский, В. Е.; Гоман, А. М.; Хиженок, В. Ф.; Петроковец, Е. М. (НТУ "ХПИ", 2009)
The PC-aided software for projection of drive with plastic gears is presented. Computation algorithm of basic parameters of gear pairs, gears, and mold diesfor plastic cylindrical and bevel gears is suggested. Depending on purpose of computation and existence of initial data one can fulfill or projecting strength design of new gear drive or make checking strength calculation for existing one. The procedure of projection strength design; calculation of gear pairand gear nominal dimensions and geometrical parameters; assignment of accuracy modes; checking guaranteed quality ratio and calculation of measured parameters taken into account appointed tolerances; computation of mold die geometrical parameters; checking strength design. Software contents, peculiarities and operations are considered too.
Keywords: геометрические параметры; показатели точности; зубчатая матрица; интервал усадки; косозубые колеса; программа "P-GEAR"; программа "P-GRUN"